Portugal [videorecording (DVD)] : wild land on the edge - Lercher, Gernot; Lurie, James (James Harrison) (PBS Distribution, 2022)
Portugal was once a great power that linked the Old and New Worlds, and this history is reflected in the country's landscapes and wildlife. Wild horses small enough to fit on cramped ships were tamed in the northern mountains and exported to Conquistadores. Now Portugal's sea horses are threatened by modern global trade.